2010
DOI: 10.1007/s00299-010-0828-6
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons

Abstract: A protocol for chloroplast transformation of an elite rapeseed cultivar (Brassica napus L.) was developed based on optimized conditions for callus induction and regeneration from cotyledonary tissues. Comparison of six different media with three elite cultivars showed that B5 medium plus 3 mg/l AgNO(3) supplemented with 0.6 mg/l 2,4-dichlorophenoxyacetic acid and 0.2 mg/l 6-furfurylaminopurine was optimal for callus formation and maintenance without differentiation, while the medium suitable for regeneration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…These results indicate that, at least up to three months after bombardment, some plasmids remained free, that is, not integrated in the genomic DNA of the transformed cells. Free plasmid DNA has also been observed in transformed cells of plants such as wheat, barley, maize and Colza (Langridge et al, 1992;Cheng et al, 2004Cheng et al, , 2010. Langridge et al (1992) stated, first, that endophytic microorganisms, such as mycoplasma associated with cereals cells, are responsible for the free plasmid-DNA observed in transgenic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that, at least up to three months after bombardment, some plasmids remained free, that is, not integrated in the genomic DNA of the transformed cells. Free plasmid DNA has also been observed in transformed cells of plants such as wheat, barley, maize and Colza (Langridge et al, 1992;Cheng et al, 2004Cheng et al, , 2010. Langridge et al (1992) stated, first, that endophytic microorganisms, such as mycoplasma associated with cereals cells, are responsible for the free plasmid-DNA observed in transgenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Langridge et al (1992) stated, first, that endophytic microorganisms, such as mycoplasma associated with cereals cells, are responsible for the free plasmid-DNA observed in transgenic cells. Then, Cheng et al (2004Cheng et al ( , 2010 indicated that the presence of free plasmid DNA may be due to the fact that the stable transformation of plant cells is progressive and, cell organelles such as chloroplasts and mitochondria are also transformed. So, in these organelles which are very close to the prokaryotes, the plasmid DNA can be free for a long time before being digested by plant endonucleases.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco was the first higher plant in which chloroplast transformation was successfully performed [31, 32]. Similarly, a protocol for plastid transformation of an elite rapeseed cultivar ( Brassica napus L.) has been developed [33]. …”
Section: Introductionmentioning
confidence: 99%
“…Plastid transformation in cauliflower (Brassica oleracea var botrytis) has been obtained at a very low frequency (Nugent et al, 2006). Plastid transformation in B. napus also has been obtained, but no homoplastomic plants could be obtained (Hou et al, 2003;Cheng et al, 2010). Plastid transformation in Lesquerella fendleri, another oilseed crop in the Brassicaceae, was feasible but inefficient (Skarjinskaia et al, 2003).…”
Section: Plastid Transformation In Arabidopsis Provides a Template Fomentioning
confidence: 99%